Quantitative “Hot-Spot” Imaging of Transplanted Stem Cells Using Superparamagnetic Tracers and Magnetic Particle Imaging - Bulte, Jeff W.M. (Tomography, 2015)
Magnetic labeling of stem cells enables their noninvasive detection by magnetic resonance imaging (MRI). In practical terms, most MRI studies have been limited to the visualization of local engraftment because other sources of endogenous hypointense contrast complicate the interpretation of systemic (whole-body) cell distribution. In addition, MRI cell tracking is inherently nonquantitative in nature. We report herein on the potential of magnetic particle imaging (MPI) as a novel tomographic technique for noninvasive “hot-spot” imaging and quantification of stem cells using superparamagnetic iron oxide (SPIO) tracers. Neural and mesenchymal stem cells, representing small and larger cell bodies, were labeled with 3 different SPIO tracer formulations, including 2 preparations (Feridex and Resovist) that have previously been used in clinical MRI cell-tracking studies. Magnetic particle spectroscopy measurements demonstrated a linear correlation between MPI signal and iron content for both free particles in homogeneous solution and for internalized and aggregated particles in labeled cells over a wide range of concentrations. The overall MPI signal ranged from 1 × 10(−3) to 3 × 10(−4) Am(2)/g Fe, which was equivalent to 2 × 10(−14) to 1 × 10(−15) Am(2) per cell, indicating that cell numbers can be quantified with MPI analogous to the use of radiotracers in nuclear medicine or fluorine tracers in (19)F MRI. When SPIO-labeled cells were transplanted in the mouse brain, they could be readily detected by MPI at a detection threshold of about 5 × 10(4) cells, with MPI/MRI overlays showing an excellent agreement between the hypointense MRI areas and MPI hot spots. The calculated tissue MPI signal ratio for 100 000 vs 50 000 implanted cells was 2.08. Hence, MPI can potentially be further developed for quantitative and easy-to-interpret, tracer-based noninvasive cell imaging, preferably with MRI as an adjunct anatomical imaging modality.